Tremor Control Devices for Essential Tremor: A Systematic Literature Review. (5th December 2019) - Castrillo-Fraile, Victoria; Peña, Elena Casas; Gabriel y Galán, José María Trejo; Delgado-López, Pedro David; Collazo, Carla; Cubo, Esther
Background: There is a growing interest in nonpharmacological approaches for essential tremor (ET), including tremor cancelation devices. However, the true efficacy of such devices in ET remains unclear. Methods: A systematic literature review was conducted using standardized criteria regarding efficacy and comfortability. Devices focused on design or experimental testing in which tremor was simulated in a robot were excluded. Results: Out of 324 articles initially identified, 12 articles were included. Orthoses using biomechanical loading and neuromodulation with electrical stimulation, and external tremor cancelation devices, were the main interventions used to suppress tremor. All devices were designed to control tremor of the upper limbs at different anatomical locations. Overall, an average tremor attenuation of 50–98% was reported (level of evidence III). Interference with voluntary movements and portability was described as the main drawback. Discussion: In conclusion, this review highlights the growing interest in emerging tremor control devices and the importance of assessing comfort without affecting voluntary movements. However, the level of evidence regarding the efficacy of these tremor control devices remains low. An integrated multidisciplinary combination approach of engineering, robotics, physiology, physiotherapy, and clinical assessment is needed to improve the quality of non-pharmacological interventions for ET.